Effect of membrane exposure on guided bone regeneration: A systematic review and meta‐analysis - Garcia, Jeffrey; Dodge, Austin; Luepke, Paul; Wang, Hom‐Lay; Kapila, Yvonne; Lin, Guo‐Hao (Clinical oral implants research, 2018)
Aims This review aimed at investigating the effect of membrane exposure on guided bone regeneration (GBR) outcomes at peri‐implant sites and edentulous ridges. Material and Methods Electronic and manual literature searches were conducted by two independent reviewers using four databases, including MEDLINE, EMBASE, Web of Science, and Cochrane Central Register of Controlled Trials, for articles up to February 2017. Articles were included if they were human clinical trials or case series reporting outcomes of GBR procedures with and without membrane exposure. A random‐effects meta‐analysis was conducted, and the weighted mean difference (WMD) between the two groups and 95% confidence interval (CI) were reported. Results Overall, eight articles were included in the quantitative analysis. The WMD of the horizontal bone gain at edentulous ridges was −76.24% (95% CI = −137.52% to −14.97%, p = .01) between sites with membrane exposure and without exposure. In addition, the WMD of the dehiscence reduction at peri‐implant sites was −27.27% (95% CI of −45.87% to −8.68%, p = .004). Both analyses showed significantly favorable outcomes at the sites without membrane exposure. Conclusion Based on the findings of this study, membrane exposure after GBR procedures has a significant detrimental influence on the outcome of bone augmentation. For the edentulous ridges, the sites without membrane exposure achieved 74% more horizontal bone gain than the sites with exposure. For peri‐implant dehiscence defects, the sites without membrane exposure had 27% more defect reduction than the sites with exposure.